2017
DOI: 10.1111/bcpt.12752
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Compared with Clopidogrel Increased Adenosine and Cyclic Adenosine Monophosphate Plasma Concentration in Acute Coronary Syndrome Patients

Abstract: Ticagrelor produces a more potent antiplatelet effect than clopidogrel and inhibits cellular uptake of adenosine, which is associated with several cardiovascular consequences. We aimed to explore the correlation between adenosine and cyclic adenosine monophosphate (cAMP) plasma concentration and antiplatelet effect by clopidogrel or ticagrelor in patients with acute coronary syndrome (ACS) receiving dual antiplatelet therapy (DAPT). We conducted a prospective, observational and single-centre cohort study enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
16
0
3
Order By: Relevance
“…Besides its antiplatelet effect, ticagrelor has a pleiotropic action and it increases plasma adenosine concentration by reducing recapturing of adenosine by red blood cells [32]. Plasma adenosine facilitates arterial vasodilatation and may decrease injury caused by reperfusion [33,34]. It has been reported that ticagrelor prescription before reper fusion, after 4 weeks of antiplatelet treatment, improved animal (a rat) heart function [34].…”
Section: Discussionmentioning
confidence: 99%
“…Besides its antiplatelet effect, ticagrelor has a pleiotropic action and it increases plasma adenosine concentration by reducing recapturing of adenosine by red blood cells [32]. Plasma adenosine facilitates arterial vasodilatation and may decrease injury caused by reperfusion [33,34]. It has been reported that ticagrelor prescription before reper fusion, after 4 weeks of antiplatelet treatment, improved animal (a rat) heart function [34].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the molecular mechanisms underlying these pleiotropic effects of ticagrelor have not been elucidated, but there is evidence suggesting that they are related to inhibition of the equilibrative nucleoside transporter-1 (ENT1) leading to increased circulating levels of adenosine and cyclic adenosine monophosphate (cAMP) [9,10]. Adenosine, by binding adenosine receptors (ARs), regulates biological processes involved in CAD and COPD progression including oxidative stress and inflammatory responses [11], and functions of monocytes, neutrophils, CD4 T-helper cells, and CD8 cytotoxic T-cells, all implicated in CAD [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The Notch pathway is regulated by cross-talks with a plethora of pathways [34,35] including the NAD + -dependent protein deacetylase, sirtuin1 (SIRT1), an oxidative stress sensor [36] and a repressor of inflammatory response [37], whose expression and activity is reduced in peripheral blood mononuclear cells (PBMCs) of stable CAD, ACS [38], and COPD [39] patients. Many studies have investigated the possible molecular mechanisms underlying the pleiotropic activity of ticagrelor in ACS [40][41][42][43] and SCAD [7] providing evidence of a ticagrelor-mediated increase in circulating levels of adenosine and cAMP [10,[44][45][46][47]. Additionally, several studies have also focused on the effects of ticagrelor on circulating inflammation markers [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Τα ανωτέρω ευρήματα προκλινικών μελετών σε σχέση με την επίδραση της τικαγκρελόρης στα επίπεδα αδενοσίνης πλάσματος, έχουν επιβεβαιωθεί και σε κλινικές μελέτες [198,199]. Ο Bonello και συν [198] [196].…”
Section: παρενέργειες αντενδείξεις και αλληλεπιδράσεις αδενοσίνηςunclassified
“…Επιλέγοντας στατιστική ισχύ 85% και αμφίπλευρο έλεγχο στατιστικής σημαντικότητας με α=0,05, συνολικά ≥48 ασθενείς απαιτούνταν για να επιτευχθεί στατιστική σημαντικότητα με βάση τις παραπάνω υποθέσεις. Η τικαγκρελόρη είναι ένα μόριο που, όπως έχει δειχθεί από αρκετές μελέτες, αυξάνει τα επίπεδα αδενοσίνης πλάσματος [198,199] και προάγει τη δράση της ενδογενούς και της εξωγενούς αδενοσίνης [192,196,200]…”
Section: υπολογισμός μεγέθους δείγματος της μελέτηςunclassified